Differential chromosome banding and isozyme assay in Corchorus aestuans L. - Alam, Sheikh Shamimul; Khatun, Masuda; Sultana, Syeda Sharmeen (Bangladesh Journal of Botany, 2011)
Karyotype of Corchorus aestuans L. was investigated with differential staining, viz. orcein, CMA and DAPI. In addition, activities of three isozyme system namely, esterase, acid phosphatase and peroxidase were studied to obtain specific molecular markers. This species was found to possess 2n = 14 metacentric chromosomes. In this species, three terminal CMA-bands appeared of which two in chromosome pairs I and the rest in a member of chromosome pair VI. Two thick DAPI-positive terminal bands were found in pair II and III. These two chromosomes showed deep CMA-negative bands at the terminal regions where DAPIpositive bands were found. Moreover, one member of pair VII fluoresced entirely with DAPI whereas an interstitial DAPI band occurred in its homologue. Five esterase, one peroxidase and two acid phosphatase bands were observed in this species. These isozyme bands were very stable and species specific. Therefore, differential fluorescent chromosome banding and isozyme assay were found to produce characteristic cytogenetical and molecular markers in C. aestuans. Key words: Fluorascent banding; Isozyme assay; Corchorus aestuans DOI: http://dx.doi.org/10.3329/bjb.v40i1.7997 Bangladesh J. Bot. 40(1): 47-52, 2011 (June)